A Self-Determined Learning Approach: Enhancing Workplace Adaptability for Overcoming Inequality - Hannes Louw; Henry Mynhardt; Sam Lubbe (Business Ethics and Leadership)
A new era of student-centered learning, fueled by the power of digital tools and advanced teaching methods, means that classrooms are no longer entirely defined by four walls and a teacher at the leadership. At the same time, the educational landscape of African countries is very slowly adapting to these changes: the traditional face-to-face approach to learning dominates, student groups are overcrowded, and there is a significant gap in digital skills between students from urban and rural areas. Today, the development of online education becomes an important prerequisite for addressing the problem of educational disparity, a tool for meeting individual educational needs, increasing students' motivation and responsibility for their learning outcomes. The Self-Determined Learning Approach allows for a personalized learning environment in which students can choose what, how and when they learn, work at their pace, choose or receive learning tasks in an order that makes sense to them, which allows for the individual interests of each student, learning style, cultural identity, life experience and personal challenges. The research is based on the results of in-depth interviews with students aged between 25 and 37 years with work (2‒5 years) and study experience, who fit the profile of self-determined learners, have part-time distance learning experience, are employed in different positions and are currently studying different programs, and are also registered with one of the three Distance Education Institutions. All participants are in their final year of study and have experienced digital transformation in distance education. This qualitative study is based on a constructivist paradigm employing a phenomenological strategy to explain the perceptions of students regarding how self-determined practices are applied at their institutions. The phenomenological approach aimed to capture the lived experiences of these students, focusing on their descriptions and interpretations of encountering self-determination practices in their educational environment. The results of the study confirmed the value of a self-determined approach to learning and its positive impact on enhancing students' workplace adaptability. However, at the same time, the survey revealed that African higher education institutions are not ready for the effective implementation of self-determined learning technologies, the main reasons being the lack of technology and the unpreparedness of teachers.